ANALISIS PENGARUH KUALITAS PELAYANAN, SARANA PRASARANA, DAN KERAGAMAN SATWA TERHADAP KEPUASAN PENGUNJUNG KEBUN BINATANG SURABAYA - Lathifa, Laily Nur; Mulyati, Awin; Mulyati, Diana Juni (Jurnal Dinamika Administrasi Bisnis, 2019)
This study aims to analyze the influence of quality, infrastructure, and diversity of animals at the Surabaya Zoo which is one of the iconic tourist attractions in the center of Surabaya. In its own development KBS has changed from year to year. The Surabaya Zoo which used to be just a place of recreation has now developed its function as a means of protection and preservation, education, research and recreation, of course. Animals that become the collection of KBS from year to year are increasing, both from domestic and abroad. Tourism objects with infrastructure, and complete diversity of animals is one reason tourists visit the Surabaya Zoo. So here researchers measure the influence to be used as a study.The population in this study were visitors who had visited the Surabaya Zoo. The measurement technique of data analysis in this study using SPSS version 16 for windows.Based on the results of tests conducted it is known that at Surabaya Zoo Service Quality, Infrastructure Facilities and Animal Diversity have a significant effect on Visitor Satisfaction.Keywords: Service Quality, Infrastructure, Animal Diversity Visitor Satisfaction.Pendahuluan